Convergence of Local Wisdom and Digital Transformation to Accelerate Tourism Village Ranking and Village SDGs - Cherly Wangkay; Eny Haryati; Amirul Mustofa (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to explore and optimize the potential convergence between local wisdom and digital transformation in accelerating the development of tourism villages and the achievement of village SDGs. The formulation of the problem raised is how to integrate local wisdom with digital technology to improve the ranking of tourism villages and support the achievement of village SDGs. The research uses a qualitative approach with data collection through in-depth interviews, field observations, and documentation. Data analysis is carried out thematically to identify patterns and relationships between the elements studied. The results of the study show that local wisdom has a vital role as a unique tourist attraction, while digital transformation plays a role in increasing the visibility and efficiency of tourism village management. Tourism villages that apply digital technology have a higher level of visits than conventional ones. The main challenges are the low digital literacy of managers and the limitations of infrastructure. In conclusion, the convergence of local wisdom and digital transformation has great potential in accelerating the development of tourism villages and achieving village SDGs. Successful implementation requires strong collaboration between the government, local communities, and the private sector, as well as increasing the capacity of managers in the use of digital technology.